Tofu-based ice cream a plant design - Reyes, Kenneth Leoncio C. (College of Engineering, 1994)
Product: Tofu-based ice cream -- Plant site: Pasig, Metro Manila -- Annual capacity: 285,314 gallons/yr -- Proposed turnover price to distributors: gallons - P 156.36, half-gallons - P 75.82, pints - P 23.27 -- Annual gross sale: P 46,526,584 -- Annual net profit: P 9,083,399 -- Total capital investment: P 14,760,160 -- Total annual production cost: P 29,823,814 -- Payback period: 0.93 yrs -- Rate of return on investment (after taxes): 61.54%